Vascular malformations : advances and controversies in contemporary management - Lee, Byung-Boong; Gloviczki, Peter; Blei, Francine; Markovic, Jovan N. (Boca Raton : CRC Press, 2020)
"This book uses evidence-based chapters to provide clarity and certainty in the clinical management of congenital vascular malformations (CVM). Each chapter written by the world authorities on each topic, reviews in depth the controversial issues in CVM management. Learn the up-to-date answer(s) on each topic"--
OCLC-licensed vendor bibliographic record.
Keywords: Cerebrovascular disease; MEDICAL / Surgery / Vascular; MEDICAL / Surgery / Thoracic; MEDICAL / Cardiology